2018
DOI: 10.1159/000493348
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Breast Carcinomas Share Prognostic Factors with Gastroenteropancreatic Neuroendocrine Tumors: A Putative Prognostic Role of Menin, p27, and SSTR-2A

Abstract: Objectives: Due to the rarity of breast carcinomas with neuroendocrine features (NEBC), the knowledge on their biology is very limited but the identification of their biology and prognostic factors is essential to evaluate both pathogenesis and possible targeted treatment options. We assessed the expression of the well-characterized prognostic factors of gastroenteropancreatic neuroendocrine tumors (GEP-NET) in NEBC. Methods: We assessed the immunohistochemical expression of neuron-specific enolase (NSE), thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Additional potential cellular targets in EP-NECs have been identified, such as in breast NEC (which is rare), farletuzumab and mirvetuximab soravtansine (FOLR1), sacituzumab govitecan (TROP-2) and HDAC inhibitors (H3K36Me3) (Vranic et al 2019). Another study reported that nuclear and cytoplasmic thymidylate synthase, nuclear and cytoplasmic neuron-specific enolase and nuclear p27 were significantly overexpressed in neuroendocrine breast carcinoma (P < 0.01); cytoplasmic somatostatin receptor-2A (SSTR-2A) expression was associated with better distant disease-free survival (P = 0.013), cytoplasmic menin expression with worse relapse-free survival (P = 0.022) and nuclear p27 with longer breast cancer-specific survival (P = 0.022), compared with invasive ductal carcinomas (Roininen et al 2019). Others targets of potential relevance are now detailed.…”
Section: New Therapeutic Perspectivesmentioning
confidence: 99%
“…Additional potential cellular targets in EP-NECs have been identified, such as in breast NEC (which is rare), farletuzumab and mirvetuximab soravtansine (FOLR1), sacituzumab govitecan (TROP-2) and HDAC inhibitors (H3K36Me3) (Vranic et al 2019). Another study reported that nuclear and cytoplasmic thymidylate synthase, nuclear and cytoplasmic neuron-specific enolase and nuclear p27 were significantly overexpressed in neuroendocrine breast carcinoma (P < 0.01); cytoplasmic somatostatin receptor-2A (SSTR-2A) expression was associated with better distant disease-free survival (P = 0.013), cytoplasmic menin expression with worse relapse-free survival (P = 0.022) and nuclear p27 with longer breast cancer-specific survival (P = 0.022), compared with invasive ductal carcinomas (Roininen et al 2019). Others targets of potential relevance are now detailed.…”
Section: New Therapeutic Perspectivesmentioning
confidence: 99%
“…Recently, Roininen et al assessed the immunohistochemical expression of well characterized prognostic factors of gastroenteropancreatic neuroendocrine tumors (GEP-NET) such as neuron specific enolase, thymidylate synthase, CD56, p27, menin, and somatostatin receptor type 2, and found a striking similarity in NEBC and GEP-NET. On the contrary, notable differences were found when compared with invasive ductal carcinomas [31].…”
Section: Prognostic Factors and Prognosismentioning
confidence: 82%
“…Interestingly, in our recent study, low MEN1 protein expression was associated with poor local relapse-free survival in breast NETs [ 4 ]. Whether the low MEN1 expression was actually due to the pathogenetic or unknown variant was not, however, addressed [ 53 ]. Pathogenetic or unknown variants in chromatin remodelling genes DAXX and ATRX are also characteristic of PNETs, and they are also frequent in other NENs [ 13 , 54 ].…”
Section: Discussionmentioning
confidence: 99%